Links Among Maternal Nutrition, Pregnancy Weight Gain, and Low Birth Weight Risk - Emi Kusumawardani; Dewi Candra Resmi; Ainal Mardiah; Nurul Amalina; Dhias Widiastuti (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
Low birth weight (LBW) represents a major contributor to neonatal morbidity and mortality. Factors related to maternal health, including gestational weight gain and nutritional condition, significantly influence fetal development and birth outcomes. This research examines the association between maternal weight gain, nutritional status, and LBW occurrence in mothers. Conducted as an analytical observational study with a case-control approach, it involved 56 participants: 28 mothers delivering LBW infants (case group) and 28 with normal-weight newborns (control group). Data were gathered from medical records and maternal health logs, then evaluated via Chi-Square testing at 95% confidence. Findings revealed a statistically significant link between maternal weight gain and LBW (p=0.016; OR=4.5), alongside maternal nutritional status and LBW (p=0.027; OR=4.231). These results emphasize the need for consistent antenatal monitoring of maternal weight and nutrition, coupled with sustained educational efforts, to reduce LBW prevalence.